Comunidad agraria y autonomías para el pueblo mapuche (1953-1972) - Samaniego Mesías, Augusto; Ruiz Rodriguez, Carlos (Revista de Historia Social y de las Mentalidades, 2011)
Alejandro Lipschutz Friedman (18831980), a physician and physiologist born in Latvia, became a Chilean citizen after coming to this country hired by the University of Concepción in 1926. He published his first ethnohistorical book in 1935 on indoamericanism. He was a world known physiologist and was awarded the first National Award for the Sciences by the Chilean state. He took part in the foundation of the Interamerican Indigenist Institute as well as in its Chilean counterpart. From the 1950’s on he interpreted the indigenous community based on a Marxist methodology and offered a view of the recognition of ethnical minorities as well as of the future of aboriginal people in the national State. Much of his research addressed